Improvement in the production of mini - antobiodies anti-gluten - Fraile Cava, Laura; López Manzano, Javier; Segovia Menacho, Patricia; Arévalo Rodríguez, Miguel; Martin Bermudo, Francisco (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2016)
Motivation: : Gluten content from very foods, like barley, rye, wheat and in certain oat varieties, must be removed in individuals with celiac disease. Immune-based assays using monoclonal antibodies specific for these immunotoxic peptides would facilitate their detection in food. Two monoclonal antibodies, G12 and A1, were developed against a highly immunotoxic 33-mer peptide.(1) In most of the Western countries, the level of gluten content in food to be considered as gluten-free products is below 20 parts per million measured by ELISA based on specific anti-gluten peptide antibody (2). The company Biomedal S.L. designed minimized single chain antibodies (scFv) in away they can produce by bacterias, which specifically recognize peptides of gluten (3). The object of this work is to improve the production and specifity of these mini-antibodies. Methods: Several techniques have been used for the production of these scFv, like cloning and purifying in different strains. Enzyme-linked immunosorbent assays (ELISAs), affinity chromatography IMAC and Western blot analysis have been carried out to measure the sensitivity of these antibodies. Results: ELISA and Western blot methods showed that most of antibodies wasn’t functional because they get degraded. Conclusions: To improve the detection of gluten by these ScFv, the production will be carried out in other strain to prevent degradation of the antibody.